Consenting Operative Orthopaedic Trauma Patients: Challenges and Solutions. (6th February 2014) - Kheiran, Amin; Banerjee, Purnajyoti; Stott, Philip
Abstract : Guidelines exist to obtain informed consent before any operative procedure. We completed an audit cycle starting with retrospective review of 50 orthopaedic trauma procedures (Phase 1 over three months to determine the quality of consenting documentation). The results were conveyed and adequate training of the staff was arranged according to guidelines from BOA, DoH, and GMC. Compliance in filling consent forms was then prospectively assessed on 50 consecutive trauma surgeries over further three months (Phase 2). Use of abbreviations was significantly reduced (P = 0.03 ) in Phase 2 (none) compared to 10 (20%) in Phase 1 with odds ratio of 0.04. Initially, allocation of patient's copy was dispensed in three (6% in Phase 1) cases compared to 100% in Phase 2, when appropriate. Senior doctors (registrars or consultant) filled most consent forms. However, 7 (14%) consent forms in Phase 1 and eleven (22%) in Phase 2 were signed by Core Surgical Trainees year 2, which reflects the difference in seniority amongst junior doctors. The requirement for blood transfusion was addressed in 40% of cases where relevant and 100% cases in Phase 2. Consenting patients for trauma surgery improved in Phase 2. Regular audit is essential to maintain expected national standards.